Chronological construction and its implications in the novel (Jurists of Darkness) - Fattah, Ali Abdel-Rahman (Al-Adab Journal, 2015)
This research is concerned with the setting of time in Saleem Barakat's novel The Scientists of Darkness . The writer , who is a famous Syrian poet , concentrates on the setting of time in his novel in which time plays a great role in it. The writer has dealt with "time" as if he is dealing with "place" which has a physical identity, giving it characteristic features of a matter in many sketches. He used the temporal techniques to establish a powerful basis of time depending on the temporal elements of flashback (analepsis) and flashforward(prolepsis). Time duration which consists of deletion, summarizing, scenery and in addition to the content of time of repeated incident and repeated manner. The researcher follows an analytical procedure keeping away from using only statistical samples for each case. And he kept the analysis away from the aesthetic spiritual aspect of literature and its semantic connotation and symbolic aspect of ideas and meanings. The researcher penetrated deeply to reach to a conclusion that will justify the purpose of the novelist behind using and repeating all these features by using a list of references at the end of the study.